A new species of the genus Clypeuspinus Balkenohl, 2021 (Coleoptera: Carabidae: Scaritinae) from India - Neethu, V.p.; Sabu, K. Thomas (Zootaxa, 2023)
The description of a new carabid species from Indian mainland belonging to the genus Clypeuspinus Balkenohl, 2021 which was formerly known in Sri Lanka. Revised generic characteristics of Clypeuspinus, and a key to species are provided.